The U.S. Public Debt : Implications for Growth - Asilis, Carlos (IMF Working Papers; Working Paper, 1994)
The increase in the U.S. public debt over the past twelve years raises questions about its implications for investment and economic growth. This paper places these developments within an international and historical context and quantitatively examines the implications of various measures of the current U.S. public debt-to-GDP ratio on economic growth. The analysis is undertaken through extensions of recently developed endogenous growth models. The results suggest that while higher levels of the public debt may affect long-run economic growth negatively, the order of magnitude is not large enough to be a cause for serious concern.